ATP indirectly stimulates hippocampal CA1 and CA3 pyramidal neurons via the activation of neighboring P2X7 receptor-bearing astrocytes and NG2 glial cells, respectively - Ying Zhang; Hai-Yan Yin; Patrizia Rubini; Patrizia Rubini; Peter Illes; Peter Illes; Peter Illes; Yong Tang; Yong Tang; Yong Tang (Frontiers Media S.A., 2022)
There is ongoing dispute on the question whether CNS neurons possess ATP-sensitive P2X7 receptors (Rs) or whether only non-neuronal cells bear this receptor-type and indirectly signal to the neighboring neurons. We genetically deleted P2X7Rs specifically in astrocytes, oligodendrocytes and microglia, and then recorded current responses in neurons to the prototypic agonist of this receptor, dibenzoyl-ATP (Bz-ATP). These experiments were made in brain slice preparations taken from the indicated variants of the P2X7R KO animals. In hippocampal CA3, but not CA1 pyramidal neurons, the deletion of oligodendrocytic (NG2 glial) P2X7Rs abolished the Bz-ATP-induced current responses. In contrast to the Bz-ATP-induced currents in CA3 pyramidal neurons, current amplitudes evoked by the ionotropic glutamate/GABAAR agonists AMPA/muscimol were not inhibited at all. Whereas in the CA3 area NG2 glia appeared to mediate the P2X7R-mediated stimulation of pyramidal neurons, in the CA1 area, astrocytic P2X7Rs had a somewhat similar effect. This was shown by recording the frequencies and amplitudes of spontaneous excitatory currents (sPSCs) in brain slice preparations. Bz-ATP increased the sPSC frequency in CA1, but not CA3 pyramidal neurons without altering the amplitude, indicating a P2X7R-mediated increase of the neuronal input. Micro-injection of the selective astrocytic toxin L-α-aminoadipate into both hippocampi, or the in vitro application of the GABAAR antagonistic gabazine, completely blocked the frequency increases of sPSCs. Hence, CA1 and CA3 pyramidal neurons of the mouse did not possess P2X7Rs, but were indirectly modulated by astrocytic and oligodendrocytic P2X7Rs, respectively.